The Effect of Acute Sleep Extension on Blood Pressure Is Dependent on the Change in Sleep Efficiency - Joaquin U. Gonzales; Cayla Clark; Jacob R. Dellinger (Clocks & Sleep)
The present study investigated the effect of acute sleep extension on blood pressure and microvascular vasodilation. Sleep and daily physical activity were objectively measured at home for two weeks using wrist actigraphy in 22 adults (60 ± 15 y). Vascular measurements were made in the morning on the 8th and 15th day. Participants spent at least 10 h in bed on the night prior to one of these testing days to extend sleep. Mean arterial blood pressure (MAP) and peak reactive hyperemia in the forearm were measured on each testing day. Reactive hyperemia and MAP were unaltered (p > 0.05) by sleep extension in the total sample. However, adults who experienced improved sleep efficiency with sleep extension (n = 10, 4.2 ± 1.4%) exhibited reduced MAP (−5.5 ± 4.6 mm Hg, p = 0.005) while adults who had little change or decreased sleep efficiency (n = 12, −1.7 ± 2.9%) showed no change in MAP. The reduction in MAP was significantly different between sleep efficiency groups (p = 0.005, Hedges’ g = 1.21) after adjustment for sex and moderate-to-vigorous physical activity. The results of this study suggest that sleep extension has the potential to reduce blood pressure in midlife to older adults when the additional sleep time improves the quality of sleep.